PEMETAAN DAERAH BERPOTENSI TRANSMIGRAN DI KECAMATAN KARTASURA DENGAN METODE FUZZY C-MEANS (FCM) CLUSTERING - Mawar Hardiyanti; Yustina Retno Wahyu Utami; Wawan Laksito Yuly Saptomo (STMIK Sinar Nusantara, 2018)
In an attempt to achieve the well-being of Indonesia, one of the Government's policies that need to be implemented are the deployment and implementation of the transmigration program. In General only a transmigration program offered by the Government to all societies without knowing the economic background and his family so that the transmigration program was not right on target. Based on the background of the problems in this research is how to design, build, develop and implement Fuzzy C-Means Clustering on Regional Mapping System for classifying the area potentially Homesteader in Kartasura. The data obtained by conducting interviews at the population administration of the subdistrict of Kartasura, observation, and study of the literature. In this research, the author uses secondary data. Data obtained from Reports in Kartasura Subdistrict number 2015 by BPS (Statistics Indonesia) Sukoharjo Regency. The results obtained are Fuzzy C-Means method can be applied to a system of mapping the area potentially Homesteader in Kartasura can optimize the work of the Government in the implementation of the resettlement program. Testing the cluster with Center validation methods using MPC alternate data criteria in the period the year 2014 and 2015 which States that 3 clusters are the cluster validation.Keywords: Classification, Fuzzy C-Means, Transmigration